2020
DOI: 10.46405/ejms.v2i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Hepatitis B Vaccination among Clinical Medical Students at a Medical College in Nepal

Abstract: Background: Hepatitis B vaccine is the single most effective and safest strategy for the prevention of the disease among health care workers (HCW), trainees and medical students. There is scanty information on knowledge, attitude and practice (KAP) regarding Hepatitis B vaccination among medical students who are likely to get exposed in the future as they start practicing. This study was undertaken to understand the knowledge, attitude and practice of hepatitis B vaccination among clinical medical students of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 10 publications
7
6
2
Order By: Relevance
“…However, the finding of this study is higher than that of the study conducted at a medical college in Nepal among clinical year medical students which showed only 29 (14.2%) of the study respondents had good practice [9] and the study conducted at Woldia University College of Medicine and Health Sciences which showed 39% of the students had good practice [5]. Such discrepancy may be due to variations in perception of the study participants towards HBV prevention, clinical practice levels, educational curriculum differences, study area and sociocultural environment and resource availability, and/or allocation discrepancies in the study areas.…”
Section: Discussioncontrasting
confidence: 91%
“…However, the finding of this study is higher than that of the study conducted at a medical college in Nepal among clinical year medical students which showed only 29 (14.2%) of the study respondents had good practice [9] and the study conducted at Woldia University College of Medicine and Health Sciences which showed 39% of the students had good practice [5]. Such discrepancy may be due to variations in perception of the study participants towards HBV prevention, clinical practice levels, educational curriculum differences, study area and sociocultural environment and resource availability, and/or allocation discrepancies in the study areas.…”
Section: Discussioncontrasting
confidence: 91%
“…In our study, 61.98% of the vaccinated participants received the full three doses 19 . In the study conducted at Manipal Medical College, only 47.1% had completed all three doses which is slightly lesser than our study 8 . Most cases of HBV infection resulting from NSSI are due to accidental percutaneous exposure, which is supported by our study findings.…”
Section: Discussionsupporting
confidence: 75%
“…Koirala Institute of Health Sciences (BPKIHS), Nepal, found that NSSI was more common in the ≤22 years age group. 8 A significant association was found between the prevalence of NSSI and the types of profession (p < 0.001) which has been supported by the studies done in other parts of Nepal (p < 0.05). 15 Our study also showed a significant difference between the prevalence of NSSI and other variables like age, sex, vaccination against HBV, and so on.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations